Bacterial vaginosis and probiotics - amiraliakbari, Sedigheh; Tafazoli, hoda (Advances in Nursing & Midwifery, 2012)
Abstract: Background and aim: Bacterial vaginosis is one of the most common infections of reproductive system ,which results from replacement of the hydrogen peroxide –producing lactobacillus species by various anaerobic bacteria. Metronidazole is the choice of treatment for bacterial vaginosis, but it has many side effects. Drug resistance and recurrent occurs in 30-50 % of patients and new treatment options are needed to improve the efficacy of present treatment. Probiotics are recommended for treatment of bacterial vaginosis. Efficacy of probiotics is discussed here. Method and materials. Electronic databases were searched for scientific publications about probiotics and bacterial vaginosis. These included: Pubmed,Ovid,Science direct and scopus. 40 publications were selected and reviewed. Results. Probiotics are live microorganisms, including Lactobacillus species, , that can be ingested and may beneficially affect the host. The mechanisms of lactobacilli function as anti-infective defenses are still not fully understood. These mechanisms may involve production of antimicrobial factors ,maintenance of a vaginal pH of ≤4.5, enhancing barrier integrity, blocking bacterial adhesion to epithelia cells ,improving immune system function producing vitamins and competing with pathogens. Probiotics can be used as probiotic yoghurt or oral capsules. Keywords ; Bacterial vaginosis,Probiotics ,Lactobacillus .